Quality of Life and Multilevel Contact Network Structures Among Healthy Adults in Taiwan: Online Participatory Cohort Study - Tso-Jung Yen; Ta-Chien Chan; Yang-Chih Fu; Jing-Shiang Hwang (JMIR Publications, 2022)
BackgroundPeople's quality of life diverges on their demographics, socioeconomic status, and social connections. ObjectiveBy taking both demographic and socioeconomic features into account, we investigated how quality of life varied on social networks using data from both longitudinal surveys and contact diaries in a year-long (2015-2016) study. MethodsOur 4-wave, repeated measures of quality of life followed the brief version of the World Health Organization Quality of Life scale (WHOQOL-BREF). In our regression analysis, we integrated these survey measures with key time-varying and multilevel network indices based on contact diaries. ResultsPeople's quality of life may decrease if their daily contacts contain high proportions of weak ties. In addition, people tend to perceive a better quality of life when their daily contacts are face-to-face or initiated by others or when they contact someone who is in a good mood or someone with whom they can discuss important life issues. ConclusionsOur findings imply that both functional and structural aspects of the social network play important but different roles in shaping people's quality of life.